Komik Fisika Isomorfis Seri Kearifan Lokal Materi Pemanasan Global Pada Tingkat SMP - Desy Kumala Sari; Marlen Leuhena; Ivylentine Datu Palittin (Musamus Journal of Science Education, 2021)
Local wisdom can be taught to learners through learning related to enviromental on IPA Terpadu subjects at the junior level. This research aims to develop a comic that has isomorphic problems. This research was designed in accordance with the research and development. The model used was 3D-E which consists of decide, design, develop, and evaluation stages. The results showed that the developed comic has quality criteria in the "good" category and declared "worthy" on material, media, and language aspects. In the future, further research is needed to test the practicality and effectiveness in the development of scientifically based physics comics of Merauke’s local wisdom which is isomorphic.